(untitled) (Journal of NELTA, 2016)
Developing any new teacher training program for Teachers’ Professional Development (TPD) should start from where the teachers are and what they actually need, which is very essential to bring out innovation and improvement in the field of ELT. The present study represents teachers’ voices from Far Western and Mid-Western part of Nepal based on the survey data collected from EFL teachers. The researcher reached to the conclusion that teachers should be trained and given opportunities on how to put the existing knowledge in to practice according to the learning context, needs and available resources creating their own context specific methodology keeping oneself up to date with global practices including the integration of ICT in the field of ELT. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:40-53